Quality of match for statistical matches used in the 1989 and 2000 LIMEW estimates for France - Thomas Masterson (Levy Economics Institute of Bard College, 2011)
The quality of match for each of four statistical matches used in the LIMEW estimates for France for 1989 and 2000 is described. The first match combines the 1992 Enquête sur les Actifs Financiers with the 1989-90 Enquête Budget de Famille (BDF). The second match combines the 1998 General Social Survey (EDT) with the 1989-90 BDF. The third match combines the 2003-04 Enquête Patrimoine with the 2000-01 BDF. The fourth match combines the 1999 EDT with the 2000 BDF. In each case, the alignment of the two datasets is examined, after which various aspects of the match quality are described. In each case, the matches are of high quality, given the nature of the source datasets.
Keywords: C14; C40; D31; 330; statistical matching; wealth distribution; time use; household production; France; LIMEW